When civil servants go frontstage: The mediatization of the role of the civil servant during the COVID-19 crisis - Birgitte Poulsen (Administrative Sciences, 2022)
Mediatization scholars have shown how institutions adapt to the penetrating role of the media. This article investigates the mediatization of the civil servant role when moving from their well-known backstage role to a frontstage role. The COVID-19 pandemic is seen as an extreme case, where some civil servants were entitled key, frontstage roles in the handling of the pandemic, compared to their normal backstage role. Thus, the pandemic has created an opportunity to study the frontstage role of civil servants as a form of mediatization. Theoretically, the study provides a conceptual framework for analyzing the mediatized role of the civil servant by linking theories on mediatization and public administration with Goffman's role theory. Empirically, the article provides an example of a hyper-mediatized civil servant during the extreme case of the COVID-19 pandemic in Denmark. The article explores how media logic entangles with the logic of bureaucracy, creating a new role for part of the civil service, resulting in governance dilemmas. The article thus contributes to the mushrooming literature on the mediatization of central government, showing the implications of a mediatized role of the civil servant, such as competition with the minister, increased vulnerability for the civil service, and blurred boundaries between administration/expertise on the one hand and politics on the other.
Keywords: 350; bureaucracy; civil servants; Goffman's role theory; media logic; mediatization